Structural Changes on Pulpwood Market in the US South: Wood Pellets Investments and Price Dynamics - Bruno Kanieski da Silva; Frederick W Cubbage; Robert C Abt (Forest Science, 2019)
We investigated the impact of wood pellet mills on pulpwood price structure in the US South. Rather than focusing exclusively on price elasticities, we progress by examining how wood pellet production has affected the spatial transmission of pulpwood prices. Pairwise price ratios were modeled using smooth transition regression to identify changes in the cointegration (linkage) between markets over time. A logistic model was fitted to estimate market linkages as a function of market distances, industry concentration, and capacity of pellet wood production. Results show that the US South is not composed of market clusters, but each market pair has a particular relation. Distance and wood pellet production capacity are the only factors driving market linkages; the pulp and paper industries did not affect market structure changes. Our research suggests spatial price transmission varies over time, and pellet mills have caused a structural change in the pulpwood prices in the US South.